EVALUASI PENERIMAAN DOSIS RADIASI PADA PEKERJA RADIASI DI INSTALASI RADIOLOGI RSUD WONOSARI - Roo'in Mas'uul, Ali; Putro, Wahyu Murti Cahyo; Marlina, Dina; Budiyono, Tris; Handoyo, Junaidi Eko (Kaunia: Integration and Interconnection Islam and Science Journal, 2023)
Radiation workers, who routinely utilize radiation sources, face a high risk due to prolonged exposure to low doses of radiation. The radiation dose for radiation workers must remain low to not exceed the specified dose limits. The specified dose limits for radiation workers is 20 mSv per year or 100 mSv within 5 years. This study aims to determine the radiation dose outcomes received by radiation workers and their correlation with the number of radiological examinations in the last 5 years at the Radiology Department of RSUD Wonosari. The research was conducted as a quantitative study with a survey approach, and the data were obtained from the receipt of film badge usage reports over a period of five years, as well as data on the number of radiological examinations conducted over the same five-year period in the Radiology Department of RSUD Wonosari. The results of the study indicate that the radiation dose received by radiology personnel at RSUD Wonosari in the last 5 years does not exceed the specified dose limits set by and has a low correlation with the number of radiology examinations conducted in the facility.